2020
DOI: 10.1111/iwj.13435
|View full text |Cite
|
Sign up to set email alerts
|

Protecting prone positioned patients from facial pressure ulcers using prophylactic dressings: A timely biomechanical analysis in the context of the COVID‐19 pandemic

Abstract: Prone positioning is used for surgical access and recently in exponentially growing numbers of coronavirus disease 2019 patients who are ventilated prone. To reduce their facial pressure ulcer risk, prophylactic dressings can be used; however, the biomechanical efficacy of this intervention has not been studied yet. We, therefore, evaluated facial soft tissue exposures to sustained mechanical loads in a prone position, with versus without multi‐layered silicone foam dressings applied as tissue protectors at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 68 publications
(203 reference statements)
2
43
0
10
Order By: Relevance
“…There were 4 studies [ 12 , [24] , [25] , [26] ] (3 case reports and 1 case-control study) identified. It was ascertained that the main sites of pressure injuries were on the forehead, chin, cheeks, lips and chest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 4 studies [ 12 , [24] , [25] , [26] ] (3 case reports and 1 case-control study) identified. It was ascertained that the main sites of pressure injuries were on the forehead, chin, cheeks, lips and chest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of severe ARDS, prone positioning of patients not only control the airways to provide mechanical invasive ventilation, but also reduce the mortality of patients [ 10 , 11 ]. The pressure injuries caused by it has been identified as the most frequent complication [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written demonstrating positive outcomes through the use of prophylactic dressings. Peko et al 6 explored the biomechanical efficacy of using prophylactic dressings, Mepilex Border Flex (Mölnlycke, Sweden). In their paper Peko et al 6 tested and evaluated how Mepilex Border Flex interacts with facial tissues of a prone head, using a computational anatomically-realistic 3D head model that reflects the shape, composition and mechanical behaviour of both the tissues and the applied dressings.…”
mentioning
confidence: 99%
“…Peko et al 6 explored the biomechanical efficacy of using prophylactic dressings, Mepilex Border Flex (Mölnlycke, Sweden). In their paper Peko et al 6 tested and evaluated how Mepilex Border Flex interacts with facial tissues of a prone head, using a computational anatomically-realistic 3D head model that reflects the shape, composition and mechanical behaviour of both the tissues and the applied dressings. They concluded that although there are limited experimental studies in the form of clinical trials investigating prophylactic dressings in the prevention of PUs for patients in the prone position, the biomechanical evidence supports the use of these dressings to reduce facial PUs during prone positioning.…”
mentioning
confidence: 99%
See 1 more Smart Citation